2017
DOI: 10.1007/s00464-017-5973-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery care versus traditional care after laparoscopic liver resections: a randomized controlled trial

Abstract: ERAS protocol is feasible and safe for laparoscopic liver resection. Patients in ERAS group have less pain and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 51 publications
3
41
0
10
Order By: Relevance
“…One way of measuring and monitoring compliance within ERAS programme is through systematic audit. 5 However, only 18.5% (5/27) of the included studies reported performing a systematic audit 20,24,27,28,40 to monitor of ERAS elements within the ERAS programme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One way of measuring and monitoring compliance within ERAS programme is through systematic audit. 5 However, only 18.5% (5/27) of the included studies reported performing a systematic audit 20,24,27,28,40 to monitor of ERAS elements within the ERAS programme.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies were RCTs, 22,25,28,29,32,35 16 were case-control studies 2, 18, 21, 23, 24, 27, 31, 33, 36-42 and five prospective studies. 19,20,26,30,34 Eleven studies included both open and laparoscopic surgery in the study, 19-21, 23, 24, 27, 33, 35, 37, 39, 40 ten studies included only open liver surgery patients, 2, 18, 25, 26, 30-32, 34, 41, 42 five studies included only laparoscopic surgery patients, 22,28,29,36,38 whilst one study performed a separate analysis for laparoscopic surgery and open surgery. 21 A detailed characteristic of included studies is shown in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Laparoscopic liver surgery (LLS) has evolved over the past two decades and is today a widely accepted standard of practice [1,2]. Recently it has been shown in randomized controlled trials that LLS is associated with significantly less postoperative complications and pain than open surgery [3,4]. In addition, LLS also showed superior cost-effectivity [3].…”
mentioning
confidence: 99%
“…Enhanced recovery after surgery (ERAS) programs have been applied for patients receiving smallscale and large-scale liver resection [13,14]. A number of studies have shown that ERAS programs are safe, feasible and effective in reducing the median LOS in both open and laparoscopic resection [15,16]. In some retrospective trials comparing earlier recovery or a reduction in LOS, perioperative evaluation or management was not uniform [12,17].…”
Section: Introductionmentioning
confidence: 99%